2012
DOI: 10.5194/bg-9-3961-2012
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution interpolar difference of atmospheric methane around the Last Glacial Maximum

Abstract: Reconstructions of past atmospheric methane concentrations are available from ice cores from both Greenland and Antarctica. The difference observed between the two polar methane concentration levels represents a valuable constraint on the geographical location of the methane sources. Here we present new high-resolution methane records from the North Greenland Ice Core Project (NGRIP) and the European Project for Ice Coring in Antarctica (EPICA) Dronning Maud Land (EDML) ice cores covering Termination 1,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
93
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 51 publications
15
93
0
Order By: Relevance
“…The inferred source changes for northern sources from recent data of Baumgartner et al (2012) (in agreement with inferences of Brook et al, 2000) suggest that northern sources were approximately halved during the last glacial period. The strong reduction in northern peatland emissions in LPJWHyMe is consistent with this inference, but it is not possible to differentiate between the boreal and subtropical northern sources using the ice-core interpolar gradient, so quantitative comparison between LPJ-WHyMe and the ice-corebased inference is difficult.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The inferred source changes for northern sources from recent data of Baumgartner et al (2012) (in agreement with inferences of Brook et al, 2000) suggest that northern sources were approximately halved during the last glacial period. The strong reduction in northern peatland emissions in LPJWHyMe is consistent with this inference, but it is not possible to differentiate between the boreal and subtropical northern sources using the ice-core interpolar gradient, so quantitative comparison between LPJ-WHyMe and the ice-corebased inference is difficult.…”
Section: Discussionsupporting
confidence: 74%
“…Ice-core data on the interpolar gradient of CH 4 as well as its isotopic signature allow for top-down estimates of the changes in sources during past climate and in general suggest that wetland emissions played a significant role in past atmospheric CH 4 variations. Recent improvements in the determination of the interpolar gradient of CH 4 from ice-core measurements suggest that low-latitude sources made the dominant contribution to abrupt changes in atmospheric CH 4 during the last glacial period (Baumgartner et al, 2012) in agreement with Brook et al (2000). This result updates older measurements by Dällenbach et al (2000) which had previously strongly implied that high-latitude sources played an important role during these abrupt events.…”
Section: P O Hopcroft Et Al: Dansgaard-oeschger Boreal Ch 4 Emissionssupporting
confidence: 78%
See 2 more Smart Citations
“…Wetlands also contribute to the atmospheric methane concentration (Baumgartner et al, 2012) and the largest supplier of methane including bogs, peatlands, swamps and marshes. It contributes one quarter of global methane emissions (Kirschke et 2000) concluded that the CH 4 production in wetlands is suffering from the acetate provide through acetate fermentation and the CO 2 reduction potential.…”
Section: Wetland Environmentsmentioning
confidence: 99%